2010
DOI: 10.1111/j.1442-2050.2009.00984.x
|View full text |Cite
|
Sign up to set email alerts
|

Prospective non-randomized study of preoperative concurrent platinum plus 5-fluorouracil-based chemoradiotherapy with or without paclitaxel in esophageal cancer patients: long-term follow-up

Abstract: Combined modality treatment for esophageal carcinoma seems to improve survival over surgery alone. Different combinations of cytotoxic drugs have been studied to improve antitumor efficacy and limit the toxicity of chemoradiotherapy (CRT) with inconsistent results. We present a prospective study of neoadjuvant CRT with or without paclitaxel in chemotherapy schedule. One hundred seven patients (93 males, 14 females), median age 59 years (range 44-76), with operable esophageal cancer were enrolled. They received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 25 publications
2
15
0
2
Order By: Relevance
“…Kelsey et al reported clinical results using PF versus paclitaxel/carboplatin/fluorouracil [19]. Disappointingly, no clear survival benefit was observed with the three-drug combinations, with significantly increased hematologic and non-hematologic toxicity, in accordance with data reported by Zemanova et al [20]. Thus, further investigations of more effective chemotherapy regimens are necessary.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Kelsey et al reported clinical results using PF versus paclitaxel/carboplatin/fluorouracil [19]. Disappointingly, no clear survival benefit was observed with the three-drug combinations, with significantly increased hematologic and non-hematologic toxicity, in accordance with data reported by Zemanova et al [20]. Thus, further investigations of more effective chemotherapy regimens are necessary.…”
Section: Discussionmentioning
confidence: 50%
“…Nevertheless, several retrospective studies have revealed that paclitaxel-based regimens did not result in superior pCR and survival compared to traditional fluorouracil-based chemotherapy [15][16][17]. The efficacy of three-drug, paclitaxel-containing regimens has been investigated as well [18][19][20]. Kelsey et al reported clinical results using PF versus paclitaxel/carboplatin/fluorouracil [19].…”
Section: Discussionmentioning
confidence: 96%
“…[147][148][149][150][151][152][153][154][155][156][157][158][159][160][161][162][163] In a recent phase I/II study, preoperative chemoradiation with a three drug regimen comprising of docetaxel, oxaliplatin, and capecitabine was safe and effective in patients with locoregional disease. 164 At a median follow-up of 116 weeks, median disease-free and overall survivals were 16 and 24 months, respectively.…”
Section: Preoperative Chemoradiation Therapymentioning
confidence: 99%
“…The patients with pN0 status had significantly longer survival compared using univariate analysis to pN+ (Figure 3). Nodal status pN0 has been reported to be a positive prognostic factor in several studies (Reynolds et al, 2007;Zemanova et al, 2010).…”
Section: Discussionmentioning
confidence: 99%